2021
DOI: 10.1088/1757-899x/1035/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Flow simulation of petroleum diesel fuel and rapeseed oil in the nozzle of a diesel injector

Abstract: The flow of petroleum diesel fuel (DF) and rapeseed oil (RO) in the nozzle of a diesel injector under operating conditions was simulated numerically. Investigated the general flow characteristics, such as mass flow rate, discharge coefficient, injection rate, averaged turbulent kinetic energy at the nozzle outlet and volume concentration of fuel vapor in the nozzle, and local flow parameters. The saturation pressure of RO is determined by summing the saturation pressure of constituting RO triacylglycerides. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Non-condensable gas soluted in liquid fuel has an impact on nozzle internal flow mainly during needle valve opening and closing (especially for pilot injection) and/or under super high injection pressure (hydraulic flip conditions). Our previous studies performed for the serial AZPI nozzle [61][62][63] showed that super-cavitation and hydraulic flips do not occur under pressure conditions corresponding to the real operating conditions of the diesel engine D243 that equips AZPI nozzles. For the investigated injection regime (corresponding to the rated operating conditions of the D243 diesel engine, see Figure 18), the main portion of the fuel (74% of cycle delivery) is injected into the cylinder when the nozzle needle is at the maximum lift.…”
Section: Flow Passage Geometry Of Nozzlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-condensable gas soluted in liquid fuel has an impact on nozzle internal flow mainly during needle valve opening and closing (especially for pilot injection) and/or under super high injection pressure (hydraulic flip conditions). Our previous studies performed for the serial AZPI nozzle [61][62][63] showed that super-cavitation and hydraulic flips do not occur under pressure conditions corresponding to the real operating conditions of the diesel engine D243 that equips AZPI nozzles. For the investigated injection regime (corresponding to the rated operating conditions of the D243 diesel engine, see Figure 18), the main portion of the fuel (74% of cycle delivery) is injected into the cylinder when the nozzle needle is at the maximum lift.…”
Section: Flow Passage Geometry Of Nozzlesmentioning
confidence: 99%
“…The accuracy assessment and validation of the numerical models used in the present study in terms of mass flow rate and cavitation distribution have been performed and given in our previous study 61 under steady flow situations and in our work 73 for dynamic injection events.…”
Section: Flow Passage Geometry Of Nozzlesmentioning
confidence: 99%